Heat Generation in Axial and Centrifugal Flow Left Ventricular Assist Devices. Issue 6 (November 2016) - Yost, Gardner; Joseph, Christine Rachel; Royston, Thomas; Tatooles, Antone; Bhat, Geetha
Abstract : Despite increasing use of left ventricular assist devices (LVADs) as a surgical treatment for advanced heart failure in an era of improved outcomes with LVAD support, the mechanical interactions between these pumps and the cardiovascular system are not completely understood. We utilized an in vitro mock circulatory loop to analyze the heat production incurred by operation of an axial flow and centrifugal flow LVAD. A HeartMate II and a HeartWare HVAD were connected to an abbreviated flow loop and were implanted in a viscoelastic gel. Temperature was measured at the surface of each LVAD. Device speed and fluid viscosity were altered and, in the HeartMate II, as artificial thrombi were attached to the inflow stator, impeller, and outflow stator. The surface temperatures of both LVADs increased in all trials and reached a plateau within 80 minutes of flow initiation. Rate of heat generation and maximum system temperature were greater when speed was increased, when viscosity was increased, and when artificial thrombi were attached to the HeartMate II impeller. Normal operation of these two widely utilized LVADs results in appreciable heat generation in vitro . Increased pump loading resulted in more rapid heat generation, which was particularly severe when a large thrombus was attached to the impeller of the HeartMate II. While heat accumulation in vivo is likely minimized by greater dissipation in the blood and soft tissues, focal temperature gains with the pump housing of these two devices during long-term operation may have negative hematological consequences.